- 6 - 7 ( c + 10 ) =
- 6 - 7 * c - 7 * 10 =
- 6 - 7 c - 70 =
- 76 - 7 c
Answer B
I really need help solving this!
For questions 6-7, simplify the expression.
6. -6 - 7(c + 10)(1 point)
A. 64 - 7c
B. -76 - 7c
C. 4 - 13c
D. -16 - 13c
I don't know which to choose, I need help solving this!
4 answers
Thank you! What about this one?
3x + 4(x-6)-3(x-7)
A.4x - 45
B.4x - 3
C.10x - 3
D.10x + 45
3x + 4(x-6)-3(x-7)
A.4x - 45
B.4x - 3
C.10x - 3
D.10x + 45
3 x + 4 ( x - 6 ) - 3 ( x - 7 )
3 x + 4 * x + 4 * ( - 6 ) - 3 * x - 3 * ( - 7 ) =
3 x + 4 x - 24 - 3 x + 21 =
4 x - 3
Answer B
3 x + 4 * x + 4 * ( - 6 ) - 3 * x - 3 * ( - 7 ) =
3 x + 4 x - 24 - 3 x + 21 =
4 x - 3
Answer B
Thank you so much! You're a big help! :)